Analysis of overhead valve push rod type valve train for off road diesel engine / Santosh A. Rane and Vilas Kalamkar - A Rane, Santosh; Kalamkar, Vilas (UiTM Press, 2010)
Push rod type valve train is still widely used for low and medium speed engines. This paper describes the methodology followed for design of valve train for new 6 cylinder turbocharged dies el engine for generating set and industrial applications. Advanced prediction tools like GT power and Matlab program were used to optimize the design. Air requirement was calculated considering air fuel ratio and thermal efficiency. Inlet valve size was finalized based on gulp factor for optimum volumetric efficiency. Valve timing was optimized to get best fuel economy and optimum emission levels using GT power model. Poly dyne cam was used for minimizing vibrations and valve jump. Ramp height is calculated using cold valve clearance and static deflection of pushrod, rocker lever, rocker shaft, rocker support and cylinder head. Valve spring was designed to take care of valve jump. Finally camshaft was designed considering torque and bending load from valve train.